A combined non‐contact acoustic thermometer and infrared hygrometer for atmospheric measurements. (5th November 2015) - Underwood, R.; Gardiner, T.; Finlayson, A.; Few, J.; Wilkinson, J.; Bell, S.; Merrison, J.; Iverson, J. J.; de Podesta, M.
ABSTRACT: Temperature and humidity measurements in the upper atmosphere are of critical importance for understanding the Earth's climate. However, such measurements are difficult for several reasons. Rising sondes carry moisture upwards, compromising measurements in the dry stratospheric environment. In addition, the difference in the time constants of thermometers and hygrometers leads to difficulties in determining the extent of saturation of the air. Finally, the effects of insolation, evaporative cooling and the poor thermal contact with the air compound the other measurement problems. To address these issues, tests on a new non‐contact temperature and humidity sensor (non‐contact thermometer and hygrometer, NCTAH), which can make rapid non‐contact measurements in atmospheric air, have been reported. The temperature and humidity measurements are made using an acoustic interferometer and a tuneable diode laser absorption spectrometer (TDLAS), respectively. This combination of sensors offers many potential advantages and allows each sensor to supply a key correction required by the other. The present study describes the design rationale and reports test results measured at the National Physical Laboratory and results from simulated ascents through the atmosphere (to −57 °C and 130 hPa characteristic of an altitude of 15 km) at the Planetary Environment Facility at the University of Aarhus, Denmark. The NCTAH makes two temperature measurements per second with a resolution of ∼0.01 °C and a likely uncertainty of measurement of u ( k = 1) = 0.1 °C. Water vapour mixing ratios were measured over a range of ∼100 to 3 x 10 4 ppmv corresponding to dew points from −42 to +24 °C at atmospheric pressure.